Peripheral memory B cells in multiple sclerosis vs. double negative B cells in neuromyelitis optica spectrum disorder: disease driving B cell subsets during CNS inflammation - Tieck, M. P.; Vasilenko, N.; Ruschil, C.; Kowarik, M. C. (Frontiers in Cellular Neuroscience, 2024)
B cells are fundamental players in the pathophysiology of autoimmune diseases of the central nervous system, such as multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD). A deeper understanding of disease-specific B cell functions has led to the differentiation of both diseases and the development of different treatment strategies. While NMOSD is strongly associated with pathogenic anti-AQP4 IgG antibodies and proinflammatory cytokine pathways, no valid autoantibodies have been identified in MS yet, apart from certain antigen targets that require further evaluation. Although both diseases can be effectively treated with B cell depleting therapies, there are distinct differences in the peripheral B cell subsets that influence CNS inflammation. An increased peripheral blood double negative B cells (DN B cells) and plasmablast populations has been demonstrated in NMOSD, but not consistently in MS patients. Furthermore, DN B cells are also elevated in rheumatic diseases and other autoimmune entities such as myasthenia gravis and Guillain-Barré syndrom, providing indirect evidence for a possible involvement of DN B cells in other autoantibody-mediated diseases. In MS, the peripheral memory B cell pool is affected by many treatments, providing indirect evidence for the involvement of memory B cells in MS pathophysiology. Moreover, it must be considered that an important effector function of B cells in MS may be the presentation of antigens to peripheral immune cells, including T cells, since B cells have been shown to be able to recirculate in the periphery after encountering CNS antigens. In conclusion, there are clear differences in the composition of B cell populations in MS and NMOSD and treatment strategies differ, with the exception of broad B cell depletion. This review provides a detailed overview of the role of different B cell subsets in MS and NMOSD and their implications for treatment options. Specifically targeting DN B cells and plasmablasts in NMOSD as opposed to memory B cells in MS may result in more precise B cell therapies for both diseases.